1990
DOI: 10.1111/j.1472-765x.1990.tb00175.x
|View full text |Cite
|
Sign up to set email alerts
|

A conductance-based surface disinfection test for food hygiene

Abstract: A surface disinfectant test method for food hygiene is described in which biocidal action was assessed using bacterial biofilms developed on stainless steel. The viability of control and surface‐bound treated biofilms was assessed, using a Malthus microbiological growth analyser. The surface test was compared with the European Suspension Test on three bacteria, Pseudomonas aeruginosa, Staphylococcus aureus and Proteus mirabilis, for 12 commonly used food surface disinfectants. In all cases the bacteria were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 9 publications
2
45
1
4
Order By: Relevance
“…We proposed that the reduction of bacterial adhesion by NAC is a chemical and biological effect. Information concerning the effect of antiadhesive coatings on the bacterial status of equipment and devices is conventionally obtained by direct methods that remove bacteria from the surface by swabbing or sonication and determine bacterial numbers by agar plating (45) or direct counting using epifluorescence microscopy (18,51). Since none of these techniques reveal the actual interaction of bacteria with the surface, it has been difficult, if not impossible, to learn more about how the coatings affect the binding between bacteria and surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that the reduction of bacterial adhesion by NAC is a chemical and biological effect. Information concerning the effect of antiadhesive coatings on the bacterial status of equipment and devices is conventionally obtained by direct methods that remove bacteria from the surface by swabbing or sonication and determine bacterial numbers by agar plating (45) or direct counting using epifluorescence microscopy (18,51). Since none of these techniques reveal the actual interaction of bacteria with the surface, it has been difficult, if not impossible, to learn more about how the coatings affect the binding between bacteria and surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have calculated the number of cells on stainless steel surfaces by relating the TTD to the equivalent number of cells, indicated by a standard calibration curve prepared from serial dilutions of planktonic cells [37,38]. Other studies of surface-inhabiting bacteria have also used calibration curves constructed from planktonic cell suspensions [39][40][41].…”
Section: Disinfection Efficacy Of Hssp Against E Coli Biofilm Estimmentioning
confidence: 99%
“…It has been shown that NaCl concentration, pH, lipid content and agar concentration affect the diffusion of different bacteriocins in an agar matrix (2). It has also been demonstrated that bacteria attached to surfaces are more resistant to disinfectants than free-living bacteria are (7,10). Williams et al (25,26) concluded that an increase in the antibiotic resistance of attached Staphylococcus aureus was due to significant physiological adaptation that occurred during the early phases of attached growth.…”
mentioning
confidence: 99%